2003
DOI: 10.1111/j.1096-0031.2003.tb00378.x
|View full text |Cite
|
Sign up to set email alerts
|

Search‐based optimization

Abstract: The problem of determining the minimum cost hypothetical ancestral sequences for a given cladogram is known to be NP-complete (Wang and Jiang, 1994). Traditionally, point estimations of hypothetical ancestral sequences have been used to gain heuristic, upper bounds on cladogram cost. These include procedures with such diverse approaches as non-additive optimization of multiple sequence alignment, direct optimization (Wheeler, 1996), and fixed-state character optimization (Wheeler, 1999). A method is proposed h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…Simmons and Ochoterena (2000) discuss gap coding at length and provide several options for treating gaps. A search-based extension of fixed state optimization, not discussed here, is implemented in POY (Wheeler, 2003). Two papers (Wheeler 1999a;Lutzoni et al, 2000) independently addressed the inclusion of ambiguously aligned regions through a procedure called fragment-level alignment (Lee 2001; see Fig.…”
Section: Gaps and Data Exclusion Criteriamentioning
confidence: 99%
“…Simmons and Ochoterena (2000) discuss gap coding at length and provide several options for treating gaps. A search-based extension of fixed state optimization, not discussed here, is implemented in POY (Wheeler, 2003). Two papers (Wheeler 1999a;Lutzoni et al, 2000) independently addressed the inclusion of ambiguously aligned regions through a procedure called fragment-level alignment (Lee 2001; see Fig.…”
Section: Gaps and Data Exclusion Criteriamentioning
confidence: 99%
“…But this method, which partitions developmental sequences in paired events, suffers from strong methodological inconsistencies and can lead to erroneous results when it comes to phylogenetic tree reconstruction or optimization of hypothetical ancestors (Schulmeister and Wheeler ). Schulmeister and Wheeler () showed that whole developmental sequences could be used instead of paired events and proposed to analyze them as a single character (i.e., one developmental sequence is treated as a single multistate character in a search‐based optimization procedure—Wheeler ). This method necessitates, however, a pool of predetermined developmental sequences to reconstruct hypothetical ancestral sequences, and thus requires untestable assumptions.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, for the Hamming and Manhattan distance, to calculate all of the tree scores in the TBR neighborhood has time complexity O (| V | 3 ) [11]. For the GTAP however, it has time complexity O (| V | 4 ) [19,22-24], or O (| V | 3 ) by increasing the hidden factor from O ( n 2 ) to O ( n 3 ) (remember that typically n ≫| V |) [20,23]. …”
Section: The Algorithmsmentioning
confidence: 99%